Determinants of employee performance: The role of workload and physical work environment - Farismawarni, Amelia; Sumbogo, Ignatius Ario (Jurnal Riset Manajemen dan Bisnis, 2023)
This research aimed to investigate the impact of work and work environment on the efficiency of staff members in a government unit in Jakarta. A quantitative approach with descriptive statistical data processing techniques was used in this study. The researcher adopted the field research method and conducted direct observations to accurately understand the conditions. 77 employees from the same department were asked to complete questionnaires to collect data. The research findings indicate that workload does not affect employee performance significantly. On the other hand, the physical work environment positively and substantially impacts employee performance.